Determining the drivers of sustainable ecotourism destination competitiveness from a supply-side perspective: a case of UNESCO World Heritage Site in Sarawak, Borneo, Malaysia - Jun Zhou Thong; May Chiun Lo; Abang Azlan Mohamad (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2024)
Over the last decade, a new segment of the tourism market has been established following the shift in global visitors’ preferences. Individuals have directed their travel course towards another form of travel, namely ecotourism. Nonetheless, the sustainability and progression of ecotourism destinations are often debated. This study involves local industry players’ perspectives, primarily to identify their perceptions towards the impacts of destination core and supporting resources on destination marketing efforts and destination competitiveness (DC). This study gathered 132 valid responses and the proposed model was evaluated using SmartPLS 4.0. Through partial least squares-structural equation modelling (PLS-SEM), the findings showed that core resources (natural resources and cultural heritage attraction) have substantial positive associations with destination marketing efforts. Supporting resources (tourism infrastructure and quality of tourism services) were found to be significantly and positively associated with DC. Interestingly, this study has revealed the absence of significant relationships between destination marketing efforts and ecotourism DC. These findings enable tourism practitioners to better understand the impacts of resources on sustainable development of ecotourism competitiveness, specifically from suppliers’ perspectives. The implications are further discussed in the paper.